Design and implementation of automated IoT security testbed. Issue 88 (January 2020) - Abu Waraga, Omnia; Bettayeb, Meriem; Nasir, Qassim; Abu Talib, Manar
Abstract: The emergence of technology associated with the Internet of Things (IoT) is reshaping our lives, while simultaneously raising many issues due to their low level of security, which attackers can exploit for malicious purposes. This research paper conducts a comprehensive analysis of previous studies on IoT device security with a focus on the various tools used to test IoT devices and the vulnerabilities that were found. Additionally, the paper contains a survey of IoT-based security testbeds in the research literature. In this research study, we introduce an open source platform for identifying weaknesses in IoT networks and communications. The platform is easily modifiable and extendible to enable the addition of new security assessment tests and functionalities. It automates security evaluation, allowing for testing without human intervention. The testbed reports the security problems of the tested devices and can detect all attacks made against the devices. It is also designed to monitor communications within the testbed and with connected devices, enabling the system to abort if malicious activity is detected. To demonstrate the capabilities of the proposed IoT security testbed, it is used to examine the vulnerabilities of two IoT devices: a wireless camera and a smart bulb.